Affirmative action as parity-inducing human resources intervention : possible applications in the South African National Defence Force - Cheminais, Jonathan Walter Albert (Stellenbosch : Stellenbosch University, 2012)
Study project (M. Admin.) -- University of Stellenbosch, 1994.